2023
DOI: 10.3390/ijms24065746
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling as a Novel Diagnostic Tool for Neurodegenerative Disorders

Abstract: There is a lack of effective diagnostic biomarkers for neurodegenerative disorders (NDDs). Here, we established gene expression profiles for diagnosing Alzheimer’s disease (AD), Parkinson’s disease (PD), and vascular (VaD)/mixed dementia. Patients with AD had decreased APOE, PSEN1, and ABCA7 mRNA expression. Subjects with VaD/mixed dementia had 98% higher PICALM mRNA levels, but 75% lower ABCA7 mRNA expression than healthy individuals. Patients with PD and PD-related disorders showed increased SNCA mRNA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…While APOE4 is not a risk factor for PD, it increases the risk of developing dementia and cognitive decline [ 77 ]. The APOE genotype also affects the age of onset and severity of stroke, and individuals with the APOE4 allele exhibit delayed recovery of verbal memory function [ 80 ] and an increased risk of developing stroke-associated dementia [ 81 ]. We and others have shown that APOE expression decreases in venous blood and plasma samples in AD patients, suggesting its potential as a diagnostic biomarker for the disease [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While APOE4 is not a risk factor for PD, it increases the risk of developing dementia and cognitive decline [ 77 ]. The APOE genotype also affects the age of onset and severity of stroke, and individuals with the APOE4 allele exhibit delayed recovery of verbal memory function [ 80 ] and an increased risk of developing stroke-associated dementia [ 81 ]. We and others have shown that APOE expression decreases in venous blood and plasma samples in AD patients, suggesting its potential as a diagnostic biomarker for the disease [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The APOE genotype also affects the age of onset and severity of stroke, and individuals with the APOE4 allele exhibit delayed recovery of verbal memory function [ 80 ] and an increased risk of developing stroke-associated dementia [ 81 ]. We and others have shown that APOE expression decreases in venous blood and plasma samples in AD patients, suggesting its potential as a diagnostic biomarker for the disease [ 81 , 82 ]. The expression of APOE mRNA is lower in E4 carriers than in individuals with APOE 2.3 and - 3.3 genotypes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often studies present contradicting results. While one meta-analysis did not find 96 changes in expression in the frontal lobe, temporal, cerebellum, or parietal lobe (Table 3), 94 another reported higher expression in AD patients across the brain. 95 Two studies investigated expression differences in blood, again with contrasting results, with one reporting higher expression in blood in patients 92 and another a reduction 96 (Table 3).…”
Section: Patients Versus Controlsmentioning
confidence: 96%
“…While one meta‐analysis did not find changes in expression in the frontal lobe, temporal, cerebellum, or parietal lobe (Table 3 ), 94 another reported higher expression in AD patients across the brain. 95 Two studies investigated expression differences in blood, again with contrasting results, with one reporting higher expression in blood in patients 92 and another a reduction 96 (Table 3 ). Finally, one study investigated ABCA7 protein expression in hippocampus and parietal cortex in individuals with different levels of Braak pathology.…”
Section: Abca7 Expressionmentioning
confidence: 99%